Experiences of Home‐Based Pulmonary Rehabilitation With mHealth and Centre‐Based Pulmonary Rehabilitation in People With Chronic Obstructive Pulmonary Disease: A Qualitative Study - Hannah Rutherford; Marita Dale; Sally Wootton; Rashmi Pithavadian; Sarah Dennis; Sarah Brown; Jennifer A. Alison; Andrew S. L. Chan; Ian A. Yang; Zoe McKeough (Health Expectations)
ABSTRACT Background Mobile health (mHealth) provides innovative solutions to improve access to pulmonary rehabilitation (PR). This study aimed to explore the experiences of people with chronic obstructive pulmonary disease (COPD) who undertook either an 8‐week home‐based PR with a mHealth application (app) (m‐PR) or centre‐based PR (CB‐PR). Methods Convenience then purposive sampling was used to recruit participants enrolled in a randomised controlled trial after completion or withdrawal from either m‐PR or CB‐PR. Participants undertook individual, semi‐structured interviews. Interview transcripts were inductively coded and thematically analysed using a critical realist approach. Results Thirteen m‐PR and 12 CB‐PR participants were interviewed (mean age (SD) 75 (8) years, 52% male). Four themes were conceptualised: internal motivators influence uptake and adherence, external motivators influence uptake and adherence, programme structure impacts practicality and experience, and living with and managing COPD and other health issues. Motivators for both programmes included improved fitness levels, feeling accountable to the programme and reinforcement from staff and peers. The m‐PR in‐app functionalities such as the daily task list were additionally motivational. m‐PR participants arranged the programme around their schedule while centred‐based participants arranged their schedule around the programme. Multi‐morbidity and illness were barriers to adherence in both programmes. The social network, environment and resources available to participants impacted their enjoyment. Conclusion This study adds important information for service providers considering implementation of mHealth PR models. Patient or Public Contribution Consumers co‐designed and user‐tested the m‐PR app. The qualitative data presented in this manuscript was obtained through interviews with consumers.